2020
DOI: 10.1049/iet-pel.2019.0506
|View full text |Cite
|
Sign up to set email alerts
|

Inrush current reduction technology of DAB converter for low‐voltage battery systems and DC bus connections in DC microgrids

Abstract: Low-voltage battery energy storage system and dual active bridge (DAB) converter control method for DC bus connection in DC microgrid. To use power efficiently in a DC microgrid, power must be easily transferred in both directions. DAB converters can easily transfer power in both directions using only the phase shift of the gate at 50% fixed duty on the primary and secondary sides. In the transient state, however, an overcurrent occurs to charge the output capacitor. A soft start algorithm is used to overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Several research activities have been focused on the control techniques of the DAB during the past few years, see [1][2][3][4][5][6][7][8][9][10][11][12][13]. A comprehensive overview of different modulation strategies of DAB converters is presented in [1].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several research activities have been focused on the control techniques of the DAB during the past few years, see [1][2][3][4][5][6][7][8][9][10][11][12][13]. A comprehensive overview of different modulation strategies of DAB converters is presented in [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors of [7] proposed a simple phase-shift modulation technique based on the parabolic carrier concept that has been implemented digitally through Verilog and hardware digital circuits. Investigators in [8,9] suggested several modulation methods for the DAB converter to avoid transformer saturation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In these systems, the energy is transferred between energy storage elements like batteries and a DC bus. Many isolated bidirectional DC–DC converters are presented in the literature for high power applications with many switches and complex control [3–9]. Some of them like dual active bridge converters operate under soft switching [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Many isolated bidirectional DC–DC converters are presented in the literature for high power applications with many switches and complex control [3–9]. Some of them like dual active bridge converters operate under soft switching [8, 9]. In low power applications, both forward and flyback topologies are employed due to their simple structure [3].…”
Section: Introductionmentioning
confidence: 99%